CCSP Self-Study : CCSP IPS Exam Certification Guide - Earl, Carter (Cisco Press, 2005)
Official self-study test preparation guide for the Cisco IPS exam 642-532 The official study guide helps you master all the topics on the IPS exam, including: IPS concepts Command-line interface (CLI) and IPS Device Manager (IDM) configuration modes Basic sensor and IPS signature configuration IPS signature engines Sensor tuning IPS event monitoring Sensor maintenance Verifying system configuration Using the Cisco IDS Module (IDSM) and Cisco IDS Network Module Capturing network traffic CCSP IPS Exam Certification Guide is a best of breed Cisco® exam study guide that focuses specifically on the objectives for the IPS exam. Cisco Security Test Engineer Earl Carter shares preparation hints and test-taking tips, helping you identify areas of weakness and improve your Intrusion Prevention System (IPS) knowledge. Material is presented in a concise manner, focusing on increasing your understanding and retention of exam topics. CCSP IPS Exam Certification Guide presents you with an organized test preparation routine through the use of proven series elements and techniques. "Do I Know This Already" quizzes open each chapter and allow you to decide how much time you need to spend on each section. Exam topic lists and Foundation Summary materials make referencing easy and give you a quick refresher whenever you need it. Challenging chapter-ending review questions help you assess your knowledge and reinforce key concepts. The companion CD-ROM contains a powerful testing engine that allows you to focus on individual topic areas or take complete, timed exams. The assessment engine also tracks your performance and provides feedback on a module-by-module basis, presenting question-by-question remediation to the text. Well-regarded for its level of detail, assessment features, and challenging review questions and exercises, this book helps you master the concepts and techniques that will enable you to succeed on the exam the first time. CCSP IPS Exam Certification Guide is part of a recommended learning path from Cisco Systems® that includes simulation and hands-on training from authorized Cisco Learning Partners and self-study products from Cisco Press. To find out more about instructor-led training, e-learning, and hands-on instruction offered by authorized Cisco Learning Partners worldwide, please visit www.cisco.com/go/authorizedtraining. Companion CD-ROM The CD-ROM contains an electronic copy of the book and more than 200 practice questions for the IPS ex ...